2014
DOI: 10.1002/anie.201311158
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Self‐Assembly of Supramolecular Charge‐Transfer Nanostructures Based on n‐Type Semiconductor‐Appended Peptides

Abstract: The reversible in situ formation of a self-assembly building block (naphthalenediimide (NDI)-dipeptide conjugate) by enzymatic condensation of NDI-functionalized tyrosine (NDI-Y) and phenylalanine-amide (F-NH2) to form NDI-YF-NH2 is described. This coupled biocatalytic condensation/assembly approach is thermodynamically driven and gives rise to nanostructures with optimized supramolecular interactions as evidenced by substantial aggregation induced emission upon assembly. Furthermore, in the presence of di-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(95 citation statements)
references
References 65 publications
6
89
0
Order By: Relevance
“…Naphthalenediimide (NDI) and its nitrogen or core modified derivatives [1][2][3] are important class of organic materials. Highly tunable visible range absorption and emission bands, [4] semiconducting behaviour (air-stable n-types emiconductor), [5][6][7] self-assembly via charget ransfer (CT) interactions with electron rich donor molecules leading to supramolecular gels (SGs) [8][9][10] and their potential in biological applications [11,12] made these class of materials particularly attractive. SGs are soft visco-elastic materials usually made from low molecular weight gelators (LMWGs); [13][14][15][16][17][18][19][20][21][22][23][24][25] these are smallm olecules having am olecular weightl ess than 3000 capable of immobilizingalarge volume of solvent within a3Dnetwork known as self-assembled fibrilar networks (SAFiNs) [26] resulting in gel.…”
Section: Introductionmentioning
confidence: 99%
“…Naphthalenediimide (NDI) and its nitrogen or core modified derivatives [1][2][3] are important class of organic materials. Highly tunable visible range absorption and emission bands, [4] semiconducting behaviour (air-stable n-types emiconductor), [5][6][7] self-assembly via charget ransfer (CT) interactions with electron rich donor molecules leading to supramolecular gels (SGs) [8][9][10] and their potential in biological applications [11,12] made these class of materials particularly attractive. SGs are soft visco-elastic materials usually made from low molecular weight gelators (LMWGs); [13][14][15][16][17][18][19][20][21][22][23][24][25] these are smallm olecules having am olecular weightl ess than 3000 capable of immobilizingalarge volume of solvent within a3Dnetwork known as self-assembled fibrilar networks (SAFiNs) [26] resulting in gel.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated the use of reversible enzymatic peptide bond formation coupled to in situ peptide self‐assembly to assist the thermodynamically controlled assembly of hydrophobic components in aqueous media. This approach was shown to be fully reversible and consequently reduces the formation of kinetic aggregates, enabling formation of functional energy transfer nanostructure, as demonstrated for supramolecular naphthalene/ peptide conjugates . We envisage that such a dynamic supramolecular scaffold can control the organization of porphyrin molecules while avoiding orthogonal assembly, directed by π–π interactions between Fmoc moiety and porphyrins …”
Section: Methodsmentioning
confidence: 93%
“…This approachw as shown to be fully reversible and consequently reduces the formation of kinetic aggregates, enabling formation of functional energy transfer nanostructure, as demonstrated for supramolecular naphthalene/ peptide conjugates. [12] We envisage that such ad ynamic supramolecular scaffold can control the organization of porphyrin molecules whileavoiding orthogonal assembly,d irected by p-p interactions between Fmoc moietya nd porphyrins. [7g, 8b, 13] Here we demonstrate the use of reversible biocatalytic selfassembly to form Fmoc-dipeptide/porphyrinc o-assembled hydrogels in aqueous medium( in pH 8p hosphate buffer) where the organization of porphyrin within the peptides caffolds can be modulated by varying the ratio of porphyrin and peptide precursor molecules.…”
mentioning
confidence: 99%
“…11,12 From a microscopic view, the supramolecular hydrogel is a three-dimensional network obtained from weak intermolecular interactions such as hydrogen bonding, p-p stacking and van der Waals forces. An efficient way to construct an aromatic-capped peptide hydrogelator is to bind an p-conjugated system such as uorenylmethoxycarbonyl (Fmoc), 13,14 naphthyl (Nap), 15,16 pentauorophenyl (PFB) 17 or naphthalene diimide (NDI) [18][19][20] to the N-terminus of a short peptide. An efficient way to construct an aromatic-capped peptide hydrogelator is to bind an p-conjugated system such as uorenylmethoxycarbonyl (Fmoc), 13,14 naphthyl (Nap), 15,16 pentauorophenyl (PFB) 17 or naphthalene diimide (NDI) [18][19][20] to the N-terminus of a short peptide.…”
mentioning
confidence: 99%
“…An efficient way to construct an aromatic-capped peptide hydrogelator is to bind an p-conjugated system such as uorenylmethoxycarbonyl (Fmoc), 13,14 naphthyl (Nap), 15,16 pentauorophenyl (PFB) 17 or naphthalene diimide (NDI) [18][19][20] to the N-terminus of a short peptide. 19,22,23 In this study, we have synthesized a new hydrogelator PFB-YF which formed a transparent hydrogel under neutral pH. In addition, Xu et al have demonstrated the rst example of the use of an enzymatic reaction to convert an phosphate group on an amino acid derivative into a neutral hydroxyl group, which readily generates a supramolecular hydrogel and as such widens the scope of this research eld.…”
mentioning
confidence: 99%